HUBUNGAN ANTARA DIABETES MELITUS TIPE 2 DENGAN KEJADIAN HIPERTENSI DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG - Rendri Bayu Hansah; Fanza Anugrah (Yayasan Nusantara Hasana Berdikari, 2026)
Type 2 diabetes mellitus is a metabolic disorder characterized by elevated blood glucose levels due to reduced insulin production by pancreatic beta cells or insulin resistance. One of the main risk factors for type 2 DM is hypertension which is interrelated because high blood pressure can reduce the sensitivity of body cells to insulin. This study aims to determine the relationship between type 2 diabetes mellitus and the incidence of hypertension at Siti Rahmah Islamic Hospital Padang. The type of research is observational with analytic method. Based on the results of data analysis obtained, it can be concluded that this study consisted of 60 samples of type 2 diabetes mellitus patients at Siti Rahmah Islamic Hospital Padang. The approach used was Cross-Sectional. The sample of this study used purposive sampling technique. Based on age characteristics, most were found at the age of 56-65 years with a total of 25 samples (41.7%), the most gender in women with a total of 31 samples (51.7%) and the most occupation in housewives with a total of 18 samples (30%). HbA1c levels in patients with type 2 DM were found to be mostly uncontrolled with 38 samples (63.3%). Hypertension was found to be most prevalent in patients with type 2 DM with 36 samples (60%). The statistical test results obtained a value of p = 0.229 (p>0.05) and r = -0.155 which means that there is no relationship between type 2 diabetes mellitus and the incidence of hypertension in the Siti Rahmah Islamic Hospital in Padang with a very weak correlation and negative correlation direction. Based on data analysis, it is found that there is no relationship between type 2 diabetes mellitus and the incidence of hypertension in Siti Rahmah Islamic Hospital Padang.